A fast-response biomimetic phototropic material built by a coordination-assisted photothermal domino strategy. Issue 10 (12th August 2022) - Tu, Zhikai; Wang, Jin; Liu, Weifeng; Chen, Zhijun; Huang, Jinhao; Li, Jinxing; Lou, Hongming; Qiu, Xueqing
Abstract : A coordination-assisted photothermal domino strategy was proposed to construct fast-response artificial phototropic materials via sequentially optimizing photothermal generation, heat conduction and thermal actuation by coordination effect. Abstract : Fast-response artificial phototropic materials are a promising tool for solar energy utilisation, yet their preparation remains challenging. Herein, we report the so-called photothermal domino strategy for constructing fast-response artificial phototropic materials. In this strategy, photothermal generation, heat conduction and thermal actuation are sequentially optimised by a coordination effect. For the first time, lignin-based organic radicals boosted by this coordination effect are used to significantly enhance photothermal conversion. Interfacial coordination bonds between lignin and an elastomer matrix promote interfacial heat conduction. Light-stimulated thermal actuation is significantly improved by coordination-assisted mechanical training. The prepared biomimetic phototropic material exhibits excellent phototropic ability, with a 2.5 s light-tracking process, showing great application potential for efficient solar energy utilisation. This strategy shows great significance for fabricating high-performance intelligent phototropic materials using widely available, green raw materials.